Chronobiological study of physiological variables and antioxidant metabolism in glicine max - Pardo DAniela (2021)
The Earth rotation exposes most of the planet's species to the environmental daily oscillations. These external oscillations synchronize the internal biological clocks that generate biological rhythms in the organisms, to anticipate the environmental changes. Among these rhythms, the circadian, 24h-rhythms, are the most studied. In plants, the initiation of photosynthesis after sunrise (periodic process) triggers the accumulation of metabolites, including the production of reactive oxygen species (ROS). ROS represent a constant threat to plants, as they react with different cellular components generating oxidative stress. However, plants have developed mechanisms to maintain redox homeostasis. The oscillations in ROS production, removal and signaling would involve the plant biological clock. The functions of clock oscillators in agriculturally important species, such as soybean (Glycine max L.), are increasingly recognized. Soybean is one of the most important and cultivated legumes in the world and constitutes the main export item of Argentina, one of the main producing countries worldwide. Therefore, the objective of this work was to study the influence of the biological clock on the physiology and antioxidant metabolism of Glycine max L. throughout a 24-hour period. For this purpose, soybean cultures were grown in hydroponics for 7 days under standard environmental conditions, with a 14h-light:10h-dark photoperiod. Biochemical (antioxidant enzyme activity, lipid peroxidation and H2O2 levels), physiological (photosynthetic pigment concentration) and molecular (primer design, identification of transcription factor binding sites) parameters, were determined in soybean leaves. Interestingly, we found that Catalase activity (p<0.05), H2O2 levels (p<0.01) and the content of chlorophyll a (p<0.01) and total chlorophyll (p<0.05) display significant daily rhythms in this tissue (Chronos-fit, p<0.05, p<0.05, p<0.05 y p<0.01, and % rhythm: 66.36%, 55.12%, 39.87%, 48.58%, respectively), with their acrophases occurring at ZT 04:18 ± 00:29, ZT 04:53 ± 00:59, ZT 10:41 ± 03:03 y ZT 10:41 ± 01:28, respectively. Even though, carotenoid content shows a significant daily variation (p<0.05), it does not adjust to a cosine curve and therefore, cannot be define as a rhythm. The 24-h oscillations showed here, might suggest the regulation of oxidative metabolism by the biological clock, in the leaves of Glycine max L. an agriculturally important plant. These results would provide useful information for plant manipulation and crop management, taking into account how antioxidant defenses and oxidative stress vary throughout the day.